Rancang Bangun Sistem Monitoring Kegiatan Akademik Siswa Menggunakan Metode User Centered Design (UCD) - Retno, Indah Pratiwi; Samsudin, Samsudin (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
The development of information technology has changed the paradigm in seeking and obtaining information, including in the context of education in Indonesia. This research aims to design and build a monitoring system for student academic activities at SD Negeri 1018886 Kiri Hilir, by applying the User Centered Design (UCD) method. The UCD method prioritizes user needs and experience, by involving admins, teachers and students in the entire planning, design and development process. The system built allows users to monitor students' academic activities in real-time via a website that can be accessed at any time. The testing method used is black box testing, which shows that the system functions as expected by the user. The test results show that the development of a student academic monitoring system using the UCD method has succeeded in producing a system that is effective and meets user needs.